The migrant public secondary school teachers in the city of Manila - Merino, Virginia Ulanday 1940-
This study involved 464 classroom teachers in 9 public high schools chosen at random from the four districts of Manila to determine the status of teachers who are not natives of Manila. Findings revealed that there are more female teachers than male teachers in Manila; 72 percent of the migrant teachers are women and 28 percent are men. The migrant teachers generally belong to the middle age group. The patronage system only partially helped the few who had letters of recommendations from important people and the migrant teachers obtained their teaching positions largely on account of their eligibilities and because teachers of their major subjects were needed. Only 25 percent had other jobs before their teaching assignment.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teacher mobility -- Philippines -- Manila; Occupational mobility